Pilonidal sinus and use of Limberg flap: a three years’ experience from two tertiary care centres of Northern India - Dogra, Varun; Mushtaq, Umer; Gilkar, Ishfaq Ahmed; Peer, Javid Ahmad (International Surgery Journal, 2022)
Background: Pilonidal sinus is a common chronic inflammatory anorectal condition that arises usually in the natal cleft of the sacrococcygeal region. This disease leads to deterioration not only in professional life of young adults but in their personal life as well. The Limberg flap reconstruction is a frequently used procedure in pilonidal sinus. This aim of this study was to observe the usefulness of Limberg flap technique in treatment of pilonidal sinus in our setup. Methods: This study enrolled a total of 50 patients who underwent Limberg flap surgery for sacrococcygeal pilonidal sinus over a period of 6 years in two different tertiary care hospitals of northern India. Various factors were studied in this study which included age group, gender, operative time, length of hospital stay, post-operative complications, recurrence and time required for return to normal work and activities. All the data was tabulated and analysed. Results: In this study we found that the maximum number of patients were young males in their third decade of life who presented with complaints of discharging sinus, pain and infection. The Limberg flap technique was used in these patients which showed a good outcome as far as complication rates and recurrence rates were concerned. Also return to work in these patients was quite early when compared with other methods in literature. Conclusions: In this study, we can conclude that this procedure is relatively easy to perform with a shorter learning curve, fewer complication rates, faster healing and is associated with a shorter hospital stay.